EFEKTIVITAS BERMAIN ORIGAMI DAN BERMAIN PLASTISIN (LILIN) TERHADAP PENINGKATAN PERKEMBANGAN MOTORIK HALUS ANAK PRASEKOLAH USIA 4-5 TAHUN - Herliana; Juniawan, Herdy; Putra, Farhandika (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2019)
Fine motor is the use of a group of small muscles such as fingers and hands that often require precisionand coordination by hand, a skill that involves the use of tools to work on an object. The development offine motor skills aims to stimulate fine motor abilities according to the stage of child development. Origamiand Plastisin (wax) is a play media that can improve the smooth motor development of children. The aim ofthis study was to determine the comparison of effectiveness playing origami and plastisin (wax) to theimprovement of fine motor development of preschool children aged 4-5 years. This study was quasiexperimental method with pre-test and post-test without control group design. The sample in this study 40respondents divided into 20 respondents intervention group 1, 20 respondents intervention group 2 withsimple random sampling technique. The result of this study was mannwhitney and wilcoxon test, obtained pvalue 0.000 (<0,05) there was difference of mean rank result in intervention group 1, intervention group 2,after treatment. The conclusion of this study, there was comparison of effectiveness of play origami andplastisin (wax) to improvement of fine motor development of preschool age 4-5 years at KindergartenAisyiyahBustanulAthfal 1 PagatanKecamatanKusanHilir Tanah Bumbu. Suggestions from this study toapply origami and plastisin (wax) as a means of learning and simultaneously for children's play activitiesthat can be used media to stimulate improvement of fine motor development of children.